CENTURIES-OLD ROOTS OF UKRAINIAN STATEHOOD - SVYATOTSKA, VICTORIA (Ehrlich’s Journal, 2024)
Scientific research is devoted to the analysis of historical facts that testify to the origin of Ukrainian statehood. The purpose of the work is to find out the period from which the countdown of Ukrainian statehood begins. The concepts of “state” and “statehood”, their mutual connection and influence are analyzed. It is argued that there is an urgent need to study the problems of Ukrainian statehood and, which is extremely important today, presenting its world through the facts of the true history of Ukraine, through the vision of history with Ukrainian eyes and without distorting Russian propaganda filters. The scientific work has found the origins, stages of origin, formation and development of Ukrainian statehood. The author analyzes the period of existence of the first state formations that arose in the territory of the Northern Black Sea in the IX century BC – VI century n. as a period when the preconditions for the emergence of Ukrainian statehood emerged. The next period of existence of Slavic proto-state entities (IV–IX centuries) is presented by the author as a period of origin, rooting of Ukrainian statehood. The conclusions are concluded that the statebuilding traditions of the Anti Union (IV–VII centuries) have become the primary source for Ukrainian statehood. The period of existence of the Eastern Slavic state of medieval Europe –Kyiv-Russian from the end of IX to the XIII centuries. The author considers as a stage of establishing, formation and development of Ukrainian statehood.